Exploring Alternative Metals to Cu and W for Interconnects Applications Using Automated First-Principles Simulations. (1st January 2015) - Sankaran, K.; Clima, S.; Mees, M.; Pourtois, G.
Abstract : The bulk properties of elementary metals and copper based binary alloys have been investigated using automated first-principles simulations to evaluate their potential to replace copper and tungsten as interconnecting wires in the coming CMOS technology nodes. The intrinsic properties of the screened candidates based on their cohesive energy and on their electronic properties have been used as a metrics to reflect their resistivity and their sensitivity to electromigration. Using these values, the 'performances' of the alloys have been benchmarked with respect to the Cu and W ones. It turns out that for some systems, alloying Cu with another element leads to a reduced tendency to electromigration. This is however done at the expense of a decrease of the conductivity of the alloy with respect to the bulk metal.